Pendidikan Kararter Tema Kearifan Lokal Melalui Permainan Tradisional dan Cerita dengan Media Wayang Golek Pada Siswa SMA N 1 Kedungwuni Pekalongan - Al Faris, Lukman; Hamisa, Wilda (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
Indonesia is a country rich in culture, even each region or tribe has its own culture. Local wisdom is the cultural wealth that exists in the area itself and is very extraordinary. Therefore, every student must be proud and not only recognize his own culture, but the role of the student must be to practice and be obliged to promote it to foreign cultures. If students do not study their own culture, it will result in a loss of national identity. This service is carried out by researchers using qualitative methods that focus on providing basic material, theories related to sub-themes such as traditional games and fairy tales using wayang golek media. It describes the ongoing service process by raising the theme of the noble cultural values of local wisdom contained in the fairy tales and traditional sports games. This activity was attended by 700 students